Defective antigen presentation by monocytes in ESRD patients not responding to hepatitis B vaccination: impaired HBsAg internalization and expression of ICAM-1 and HLA-DR/Ia molecules - J. Stachowski; C. Barth; M. Pollok; J. Michalkiewicz; K. Madalinski; J. Maciejewski; C. A. Baldamis (Hindawi Limited, 1995)
This study was undertaken to evaluate the monocyte function of uraemic non-responders to hepatitis B vaccination. Therefore, some parameters concerning antigen processing by monocytes (Mo) as antigen presenting cells (APC) were analysed. It was found that in uraemic non-responders, (1) the internalization of HBsAg by monocytes was significantly decreasjed-HBsAg complexed with specific IgG or as immune complex isolated from patients is better internalized compared with free HBsAg; (2) during antigen presentation the expression of adhesion (ICAM-1) and accessory (HLA-DR/Ia) molecules was significantly decreased in uraemic patients, especially in non-responders; and (3) impaired internalization of HBsAg as well as a decrease in ICAM-1 and HLA-DR/Ia expression, correlated well with the blunted proliferation of CD4+ T cells stimulated by autologous monocytes induced by HBsAg.